Priseljevanje in društveno delovanje Slovencev v drugih delih jugoslovanskega prostora Zgodovinski oris in sedanjost - Žitnik Serafin, Janja (ZRC SAZU, Založba ZRC, 2014)
Immigration of Slovenians to other areas of the former Yugoslavia and their organization of ethnic societies there is a subject of research that became interesting for researchers in the field of international migration studies only after the disintegration of the former Yugoslavia. Compared to the research into Slovenian immigration to other countries and continents, this subject had been neglected for decades. The book ('Slovenian Immigration and Society Activities across the Former Yugoslavia: Historical Outline and the Present') is divided into three chronological parts: Historical Outline, Between the Past and the Present, and The Current Situation. In this book, the data and findings of previous research are revised, upgraded and completed by the results of the authors' own archival and statistical research as well as extensive fieldwork (questionnaire, half-structured interviews, meetings/roundtables, informal interviews, observation with participation), carried out in the framework of two research projects.